Bioactive interactions, physicochemical and health-promoting qualities of pro-milk extract and flour derived from processed seeds from Hura crepitans and Citrullus colocynthis - Israel Sunmola Afolabi; Ajuma Lydia Ugbabe; Karis Akunna Nwachukwu; Chidiebube Emmanuel Eberechi; Morolake Edna Olaitan; Eze Frank Ahuekwe; Oluwatofunmi E. Odutayo; Alaba Oladipupo Adeyemi (Heliyon)
Fermentation is an age-old biotransformation technique for creating stable and safe food products. The study derived flour and a milky extract from 1, 3, and 5-day fermented Hura crepitans and assessed their edibility and bioactive properties compared to melon (Citrullus colocynthis). It assessed their edibility, transformation, nutritional, and bioactive phytochemicals, compared with the corresponding edible properties of melon and those of another food processing technique (boiling). Also assessed was the role of probiotic bacteria- Enterococcus faecalis-aided submerged fermentation as an instrument to improve the interactions of bioactive-phytochemicals and health benefits of the pro-milk extract and flour derived from the Hura crepitans seeds with melon seeds and boiling serving as controls. The flour yield from the seed of H. crepitans increased significantly (P < 0.05) after fermentation compared to that of C. colocynthis. Fermentation and boiling significantly enhanced (P < 0.05) the flour yield and free radical scavenging capacity of the seeds from H. crepitans. Fermentation significantly increased (P < 0.05) the lactate dehydrogenase activity (LDH) activity, vitamin C, sodium, potassium, and terpenoids of the seeds from H. crepitans and vitamin A, vitamin E, sodium, calcium, and iron in melon seeds. Boiling alone significantly increased (p < 0.05) the yield, DPPH radical scavenging capacity, and flavonoids of the seeds from H. crepitans and significantly reduced (p < 0.05) the Hue value (h°) for the pro-milk and LDH of the seeds from H. crepitans. The natural seeds of H. crepitans possess significantly lower (p < 0.05) h° for flour, vitamin B9, and bioflavonoids than the natural melon seeds and significantly higher (p < 0.05) h° for pro-milk, bacteria count, vitamin A, and ash than the melon seeds. Aescin (35.09 mg/kg), p-coumaric acid (64.78 mg/kg), and resorcinol (50.18 mg/kg) constitute the most prominent saponin, phenolic, and bioflavonoids. Fermented H. crepitans are rich sources of essential and bioactive nutrients broadly comparable to melon seeds. It is a potential food source for human consumption.